Análisis de los Valores en los Consumidores de la Ciudad de Saltillo, Coahuila, México, 2018 - Wong, Adriana Méndez; Ruiz, Edith Reyes; Siller, Jesús Francisco Mellado; Ramirez, Karina Lizbeth Rodriguez (European Scientific Journal, ESJ, 2018)
This paper focuses on the Consumer Behavior area in Saltillo, Coahuila, Mexico. It is an exploratory, descriptive, quantitative, and transversal study. Even if the study of the values is not new, the reality is that there is an interest to describe the profiles of the consumers under this perspective. Using the List Of Values (LOV) (Kahle, Beatty & Homer, 1986) cited by Irene Ramos Soler (2008), this scale has been used in the investigation of various market segmentation and in identifying various marketing goals. The questions were categorical and the answers were indicated on the Likert scale from 1 to 9. 1000 valid questionnaires were distributed with a response rate of 95%, validating the appliance with a Cronbach alpha of 0.809. The answers to the empirical work show that the most important value for the people living in Saltillo is â€œRespect to othersâ€.